Effectiveness of Standing Frame on Constipation in Children with Cerebral Palsy: A Single‐Subject Study. (16th May 2014) - Rivi, Elena; Filippi, Mariacristina; Fornasari, Elisa; Mascia, Maria Teresa; Ferrari, Adriano; Costi, Stefania
Abstract Children with cerebral palsy (CP) and quadriplegia or severe diplegia suffer from highly reduced mobility and consequent constipation. Clinicians recommend standing frames to exercise the support reaction in this population, sharing the opinion that the upright position may facilitate intestinal transit, although no evidence supports this assumption. We conducted this study to determine the effects of the standing frame on spontaneous evacuation in children with CP. Moreover, we studied its effects on the frequency of induction of evacuation, the characteristics of the stool and the pain suffered by the child due to constipation and/or evacuation. We implemented a single‐subject research design in one chronically constipated child with CP and quadriplegia, Gross Motor Function Classification System Level V. To monitor the effects of the standing frame, we measured the outcome of interest throughout the study using a daily diary and the Bristol Stool Scale. This study was approved by the local Ethics Committee. This study has several limitation; primarily, the use of a single‐subject research design only makes possible the visual analysis of data obtained from a unique patient. So, by themselves, data obtained do not allow us any generalization for the target population. Future research should verify our results collecting more data and also investigating the effect of the standing‐frame on respiratory functions. Although the standing frame did not affect the frequency of evacuations or the characteristics of the stool, its employment reduced the inductions of evacuation and the related pain suffered by the child. However, this study has several limitations, such as the lack of generalization due to the fact that we studied a unique patient and the overall brevity of the study due to external circumstances. Therefore, we suggest future research to verify our results, also investigating the effect of the standing frame on respiratory functions. Relevance to clinical practice. The standing frame may positively influence the management of constipation of these children, possibly improving their quality of life. Copyright © 2014 John Wiley & Sons, Ltd.